Ecclesiastic Architecture of the First Bulgarian Kingdom: Researchers and Research - Maltseva, Svetlana V. (Actual Problems of Theory and History of Art, 2019)
The paper deals with the history of research on the ecclesiastic architecture of the First Bulgarian Kingdom. The main stages of this process are described, starting from the first ethnographic expeditions of the 1880s and first archaeological investigations of the 1890s to the modern times. Analyzing the methods of research on Bulgarian monuments the author shows that throughout the 20th century the interpretations of facts and archaeological finds have not always been free from changing ideological concepts.
Keywords: First Bulgarian Kingdom; medieval Bulgarian architecture; Byzantine architecture